Sistem Pakar Diagnosa Penyakit pada Anjing Menggunakan Metode Forward Chaining dan Certainty Factor - Kevin Shaquille Limanuel; Leo Willyanto Santoso; Silvia Rostianingsih (Universitas Kristen Petra, 2022)
Dogs' diseases have different treatments which affect the owner on how to treat them. If the treatment given is not proper, even a minor disease could be fatal, which will be very detrimental to the dog owner and also the dog itself. The problem that the author wants to address is by utilizing a website that functions to diagnose common dog disease by using an expert system based on the forward chaining method and the certainty factor method to diagnose if there are any symptoms in dogs. Tests were also carried out on a collection of interview data and also from the expert in the form of disease symptoms and the program that was made are able to diagnose dog disease with the results of the method test being able to achieve an accuracy value of 80%.